2000
DOI: 10.1164/ajrccm.161.1.9904110
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust Particles Activate p38 MAP Kinase to Produce Interleukin 8 and RANTES by Human Bronchial Epithelial Cells and N-Acetylcysteine Attenuates p38 MAP Kinase Activation

Abstract: Air pollutants including diesel exhaust particles (DEPs) have been shown to enhance allergic responses. DEPs stimulate airway epithelial cells to produce various cytokines; however, the intracellular signal transduction pathway and the involvement of reduction and oxidation (redox) control in DEP-activated signaling have not been determined. In the present study, we therefore examined the role of p38 mitogen-activated protein (MAP) kinase in DEP-induced interleukin 8 (IL-8) and RANTES production by human bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
3
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 32 publications
4
84
3
1
Order By: Relevance
“…In the literature, the effect of NAC on p38 MAPK is cell type-dependent; in human bronchial epithelial cells, NAC did not affect influenza virus infection-induced increases in p38 MAPK phosphorylation [17], but in other cell types such as in human pulmonary vascular endothelial cells, there is some evidence that NAC affects the activation of p38 MAPK [14,18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the literature, the effect of NAC on p38 MAPK is cell type-dependent; in human bronchial epithelial cells, NAC did not affect influenza virus infection-induced increases in p38 MAPK phosphorylation [17], but in other cell types such as in human pulmonary vascular endothelial cells, there is some evidence that NAC affects the activation of p38 MAPK [14,18].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, ROS seem to be involved in the activation of p38 MAPKs in different cell types, such as vascular smooth muscle cells [11,26,27] and bronchial epithelial cells, stimulated with diesel exhaust particles [18].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that these sterile stimuli all signal through the IL-1RI could suggest that pollutants stimulate lung inflammatory responses through a common IL-1RI-dependent mechanism (5). However, DEP inhalation can also induce chemokines, like KC, directly from the epithelium (22). Probably, this explains the limited, but increased, pulmonary inflammation in DEP-exposed IL-1RI KO mice when compared with saline-exposed IL-1RI KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorbed organic compounds have been implicated in many of the systemic and molecular responses of respiratory system cells exposed to diesel exhaust particles (3)(4)(5)(6). Studies with residual oil fly ash (ROFA) particles have demonstrated a role for particleassociated metals in inducing inflammatory responses in respiratory cells (7,8).…”
mentioning
confidence: 99%